Pengaruh Gaya Kepemimpinan General Manager Terhadap Kinerja Karyawan di Kharisma Hotel Bukittinggi - Fakhrul Rozy Ms; Pasaribu Pasaribu (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2020)
Abstract The objectives of the research are to find out determine the effect of the general manager's leadership style on employee performance at Kharisma Hotel Bukittinggi. This research was conducted on 38 employees of Kharisma Hotel Bukittinggi who were respondents, data collection was done by questionnaire. Sampling is determined using the Total Sampling technique. Data collection is done by distributing questionnaires to respondents and using secondary data from the hotel. The analysis technique in this study uses simple linear regression analysis. The data in this study were processed with SPSS version 21. The results of this study showed leadership style had a positive and significant effect on employee performance at Kharisma Hotel Bukittinggi.